Comparison of mifepristone plus misoprostol with misoprostol alone for first trimester medical abortion: A systematic review and meta-analysis - Tariku Shimels; Melsew Getnet; Mensur Shafie; Lemi Belay (Frontiers Media S.A., 2023)
ObjectiveTo compare mifepristone plus a misoprostol-combined regimen with misoprostol alone in the medical abortion of first trimester pregnancy.MethodsAn internet-based search of available literature was performed using text words contained in titles and abstracts. PubMed/Medline, Cochrane CENTRAL, EMBASE, and Google scholar were used to locate English-based articles published until December 2021. Studies fulfilling the inclusion criteria were selected, appraised, and assessed for methodological quality. The included studies were pooled for meta-analysis, and the results were presented in risk ratio at a 95% confidence interval.FindingsNine studies comprising 2,052 participants (1,035 intervention and 1,017 controls) were considered. Primary endpoints were complete expulsion, incomplete expulsion, missed abortion, and ongoing pregnancy. The intervention was found to more likely induce complete expulsion irrespective of gestational age (RR: 1.19; 95% CI: 1.14-1.25). The administration of misoprostol 800 mcg after 24 h of mifepristone pre-treatment in the intervention group more likely induced complete expulsion (RR: 1.23; 95% CI: 1.17-1.30) than after 48 h. The intervention group was also more likely to experience complete expulsion when misoprostol was used either vaginally (RR: 1.16; 95% CI: 1.09-1.17) or buccally (RR: 1.23; 95% CI: 1.16-1.30). The intervention was more effective in the subgroup with a negative foetal heartbeat at reducing incomplete abortion (RR: 0.45; 95% CI: 0.26-0.78) compared with the control group. The intervention more likely reduced both missed abortion (RR: 0.21; 95% CI: 0.08-0.91) and ongoing pregnancy (RR: 0.12; 95% CI: 0.05-0.26). Fever was less likely to be reported (RR: 0.78; 95% CI: 0.12-0.89), whereas the subjective experience of bleeding was more likely to be encountered (RR: 1.31; 95% CI: 1.13-1.53) by the intervention group.ConclusionThe review strengthened the theory that a combined mifepristone and misoprostol regimen can be an effective medical management for inducing abortions during first trimester pregnancy in all contexts. Specifically, there is a high-level certainty of evidence on complete expulsion during the early stage and its ability to reduce both missed and ongoing pregnancies.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42019134213, identifier CRD42019134213.